2001
DOI: 10.1007/s003840100313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caseload on the short-term outcome of colon surgery: results of a multicenter study

Abstract: This prospective multicenter study investigated the effect of hospital caseload on early postoperative outcome of surgery for carcinoma of the colon in 75 German hospitals and included 2293 patients. The hospitals were divided into those with a caseload of 1-30 (group A), 31-60 (group B), and more than 60 (group C) operations. Increasing caseload was associated only with fewer general postoperative complications. It was also associated with significantly greater use of antibiotic prophylaxis. No significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
12

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 72 publications
1
23
1
12
Order By: Relevance
“…Although there were no major differences in perioperative care and patient recovery after elective colonic surgery between European and US patients [22], postoperative length of stay was only 7 days in the United States but 10–13 days in European countries. In Germany, the postoperative hospital stay after colonic cancer surgery is as long as 17 days [24], and even patients undergoing laparoscopic colonic resection remain in hospital for 11–12 days after surgery [25]. Factors other than patient recovery which are responsible for the traditionally prolonged stay in German hospitals include: the reimbursement system hardly ever penalizes postoperative hospital stay; general practitioners are reluctant to treat patients who are discharged early after surgery; many hospitals do not have adequate outpatient facilities to take care of these patients; surgeons fear major complications after discharge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no major differences in perioperative care and patient recovery after elective colonic surgery between European and US patients [22], postoperative length of stay was only 7 days in the United States but 10–13 days in European countries. In Germany, the postoperative hospital stay after colonic cancer surgery is as long as 17 days [24], and even patients undergoing laparoscopic colonic resection remain in hospital for 11–12 days after surgery [25]. Factors other than patient recovery which are responsible for the traditionally prolonged stay in German hospitals include: the reimbursement system hardly ever penalizes postoperative hospital stay; general practitioners are reluctant to treat patients who are discharged early after surgery; many hospitals do not have adequate outpatient facilities to take care of these patients; surgeons fear major complications after discharge (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that "medium-volume" surgeons achieved excellent outcomes similar to "high-volume" surgeons when operating in "medium-volume" or "highvolume" hospitals, while the results of "low-volume" surgeons improved with increasing hospital volume but never reached those of the "high-volume" surgeons [6]. In contrast, Marusch et al [7] failed to show significant associations between hospital caseload and postoperative outcome in 2,293 colorectal cancer patients undergoing surgery.…”
Section: Introductionmentioning
confidence: 98%
“…Auf die statistische Auswertung wichtiger Einzelaspekte und Outcome-Kriterien wurde verzichtet [17,18,19].…”
unclassified